Prevalence of undiagnosed subchondral insufficiency fractures of the knee in middle age adults with knee pain and suspected meniscal tear. Issue 4 (December 2020) - Huizinga, Jamie L.; Shah, Nehal; Smith, Stacy E.; Notino, Anthony; Kluczynski, Melissa A.; Jordan, Kelly; Bisson, Leslie J.; Chen, Antonia F.; Selzer, Faith; Losina, Elena; Katz, Jeffrey N.
Abstract: Objective: Symptomatic knee osteoarthritis (OA) and meniscal tear are often treated with weight-bearing exercises and without ordering advanced imaging (e.g. MRI). This may lead to missed diagnoses of subchondral insufficiency fracture of the knee (SIFK). Failure to diagnose SIFK has treatment implications, as patients with SIFK are typically managed with a period of reduced weight-bearing. The primary objective of this study is to determine the prevalence of undiagnosed SIFK among persons treated non-operatively for knee pain and suspected meniscal tear(s). Methods: The randomized controlled trial, TeMPO (Treatment of Meniscal Problems and Osteoarthritis), enrolls subjects whose clinicians suspect concomitant meniscal tear and knee OA. TeMPO participants undergo MRI ordered by the study to confirm meniscal tear. All study-ordered MRIs revealing a fracture were reviewed by two study radiologists who noted features of the fracture and joint. We report prevalence of SIFK and clinical and imaging features on these subjects with 95% confidence intervals. Results: Ten of the 340 study-ordered MRIs had SIFK, resulting in an estimated prevalence of 2.94% (95% CI: 1.15%, 4.71%). Eight of the ten participants with SIFK had fractures located medially. The femur was involved in five of these participants, tibia in four, and both in one. Five of the ten participants did not have meniscal tears. Conclusions: This is the only reported estimate of undiagnosed SIFK in adults with knee pain, to our knowledge. Approximately 3% of patients managed with weight-bearing exercise for suspected meniscal tear may have SIFK, a diagnosis typically treated with reduced weight-bearing approaches.